Respuesta :
Answer:
Given f(x) and g(x), please find (fog)(X) and (gof)(x) f(x) = 2x g(x) = x+3
Given f(x) and g(x), please find (fog)(X) and (gof)(x)
f(x) = 2x g(x) = x+3
print Print document PDF list Cite
Quick Answer
(fog)(x) = 2x + 6
(gof)(x) = 2x + 3
Expert Answers
HALA718 eNotes educator| CERTIFIED EDUCATOR
f(x) = 2x
g(x) = x + 3
First let us find (fog)(x)
(fog)(x) = f(g(x)
= f(x+3)
= 2(x+3)
= 2x + 6
==> (fog)(x) = 2x + 6
Now let us find (gof)(x):
(gof)(x) = g(f(x)
= g(2x)
= 2x + 3
==> (gof)(x) = 2x + 3
Step-by-step explanation:
Answer:
(gof)(x) = 6x
Step-by-step explanation:
We have given two function and we have to find their function.
f(x) = 3x and g(x) = 2x
(gof)(x) = ?
The formula to find the composition of two function:
(gof)(x) = g(f(x))
Putting the values of given functions ,we get
(gof)(x) = g(3x)
(gof)(x) = 2(3x)
(gof)(x) = 6x which is the answer.